Algoritma Media Sosial: Urgensi Pendidikan Dakwah dalam Platform Digital Youtube - Nauva Auliyatul Faizah; Nijma Auliah Salsadilah; Elok Atika (Al-Kindi, 2025)
Technological advances have brought about major changes in the dissemination of Islamic information. Social media has become the main means of disseminating da'wah content, including Islamic studies in the form of videos, photos, and live broadcasts. However, behind this convenience, a serious challenge arises in the form of the dissemination of unvalidated information due to social media algorithms that prioritize user engagement over content veracity. This research uses a qualitative approach with a library research approach. Data sources collected included books, journals, and Islamic preaching videos on the social media platform YouTube.This study aims to examine how social media algorithms filter, disseminate, and shape Islamic understanding, and emphasizes the importance of information validation to reduce misinformation. By referring to previous research and offering new perspectives, this study is expected to encourage the formation of a healthier and more responsible digital ecosystem in spreading Islamic narratives